PENETAPAN KADAR KLORIN PADA BEBERAPA MERK PEMBALUT WANITA YANG ADA DI PASARAN DENGAN METODE IODOMETRI - Daulay, Anny Sartika; Lubis, Minda Sari; Sandika, M Teguh (Jurnal Farmanesia, 2017)
Sanitary napkin is a device product used by women during menstruation, sanitary napkins function to absorb blood from the vagina so that the blood that comes out does not interfere. Currently, there are many problems that arise in sanitary napkins, due to the presence of chlorine additives which function as an ingredient in the initial bleaching process of sanitary napkins. The purpose of this study was to identify the color reaction test, and to determine the chlorine content by iodometry method in sanitary napkins on the market. This research is an experimental study using a sample of sanitary napkins on the market. Sampling by random sampling (random). Determination of chlorine in sanitary napkins by testing qualitatively with a color reaction and quantitatively using the iodometric method.Based on the results of the study, it was found that of the 5 (five) samples used, 3 (three) positive samples contained chlorine, namely samples A, B and sample C. The chlorine content obtained in sample A was 0.0035%, sample B was 0.0014 % and sample C is 0.0027%. According to YLKI, the normal threshold for the use of chlorine in sanitary napkins is 5-55 ppm, so the samples tested still meet the stipulated conditions.